Theoretical And Methodological Foundations Of Teaching Russian In Non-Specific Educational Fields Of Pedagogical Universities - Нарзуллаева Умида Ильхомовна (Periodica Journal, 2025)
Teaching Russian in non-specific educational fields of pedagogical universities is a complex of scientific and practical approaches aimed at the formation of linguistic and communicative competencies of future teachers. The Russian language not only serves as a means of communication, but also represents the key to the culture, history and traditions of the Russian people. This article examines the theoretical and methodological foundations of teaching Russian, including goals, methods, approaches and current trends. new teaching methods and technologies to provide high-quality education in the field of the Russian language for both native speakers and those who study it as a foreign language.
Keywords: Non-specific educational fields; pedagogical universities; teaching methods